ANALISIS HARGA SAHAM DAN EARNING PER SHARE (EPS) TERHADAP BID ASK SPREAD PADA SAHAM SYARIAH PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI ISSI PERIODE 2014 - 2017 - Anggraeni Dwi Briliantini; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to analyze the effect of stock prices and earnings per share on bid ask spread on sharia shares of property and real estate companies listed in ISSI for the period 2014-2017 both partially and horizontally. This study uses a population of property and real estate companies registered at the ISSI. This study uses a sample of 26 samples of property and real estate companies registered with the ISSI where the sampling technique uses purposive sampling technique. The observation period in this study starts from the period 2014 - 2017. Based on the results of the study, the best estimation model used is the common effect model (CEM), this indicates that the variable share price and earnings per share (EPS) have a significant and simultaneous influence towards bid ask spread of sharia shares of property and real estate companies registered in ISSI for the period 2014 - 2017. The results of the research partially indicate that the stock price variable has a significant negative effect on the bid ask spread of sharia stock property and real estate companies registered in the ISSI period 2014-2017, while the earnings per share (EPS) variable has no influence and is significant towards bid ask spread of sharia shares of property and real estate companies registered in ISSI for the period 2014 - 2017.Keywords: Stock Price, Earning Per Share (EPS), property and real estate companies, ISSIREFFERENCESAmbarwati. Sri Dwi Ari. 2008. Pengaruh return saham, volume perdagangan saham, varian return saham terhadap bid ask spread saham pada perusahaan manufaktur yang tergabung dalam Indeks LQ 45 tahun 2003 – 2005. Jurnal Siasat Bisnis. Vol. 12, No.1.Ewijaya dan Nur Indriantoro. 1999. Analisis Pengaruh Pemecahan Saham terhadap Perubahan Harga Saham. Jurnal Riset Akuntansi Indonesia, 2(1) : 53 65.Griffith, W.E. 2001. Undergraduate Econometrics. Cetakan kedua. Jhon Willey and Sons, Inc.Hidayat, Taufik. 2011. Buku Pintar Investasi Syariah.Jakarta : PT TransMediaHusnan, Suad. 2009. Dasar – dasar Teori Portofolio dan Analisis Sekuritas Edisi Keempat. Yogyakarta : LPP STIM YKPN.Napitupulu, Veronica dan Syahyunan. 2013. Pengaruh Return Saham, Volume Perdagangan Saham, dan Volatilitas Harga Saham Terhadap Bid Ask Spread Pada Perusahaan yang Melakukan Stock Splitdi Bursa Efek Indonesia. Jurnal Media Informasi Manajemen, Vol 1 No. 2, April 2013.Rasyidi, Leoni B. dan Yunika Murdayanti. 2013. Pengaruh asset size, closing price, likuiditas, varian return, dan volume perdagangan saham terhadap bid ask spread pada perusahaan real estate dan property yang terdaftar di BEI. Accounting Analysis Journal. Vol. 8, No.2.Ryandono, Muhammad Nafikh H. 2009. Bursa Efek dan Investasi Syariah. Jakarta : Serambi.Sartono. Agus. 2001. Manajemen Keuangan Teori dan Aplikasi. Edisi Keempat. Yogyakarta : BPFE.Stoll. Hans R. 1989. Infering The Component Of The Bid Ask Spread : Theory and Empiricial Test. The Journal of Finance. Vol.4, No. 1.Sugiyono. 2012. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Cetakan ke-XVII.Bandung: Alfabeta.Sugiyono. 2014. Metode Penelitian Bisnis. Bandung : Alfabeta.Tambunan, Andy Porman. 2007. Menilai Harga Wajar Saham (Stock Valuation). Jakarta : PT Elex Media Komputindo.Tandellin, Eduardus. 2010. Portofolio dan Investasi Teori dan Aplikasi. Yogyakarta : KanisiusSITUS RESMIhttps://www.ojk.go.id http://www.idx.co.id